Indoor location based services challenges, requirements and usability of current solutions - Basiri, Anahid; Lohan, Elena Simona; Moore, Terry; Winstanley, Adam; Peltola, Pekka; Hill, Chris; Amirian, Pouria; Figueiredo e Silva, Pedro (Elsevier, 2017)
Indoor Location Based Services (LBS), such as indoor navigation and tracking, still have to deal with both technical and non-technical challenges. For this reason, they have not yet found a prominent position in people’s everyday lives. Reliability and availability of indoor positioning technologies, the availability of up-to-date indoor maps, and privacy concerns associated with location data are some of the biggest challenges to their development. If these challenges were solved, or at least minimized, there would be more penetration into the user market. This paper studies the requirements of LBS applications, through a survey conducted by the authors, identifies the current challenges of indoor LBS, and reviews the available solutions that address the most important challenge, that of providing seamless indoor/outdoor positioning. The paper also looks at the potential of emerging solutions and the technologies that may help to handle this challenge.